The use of alcoholic beverages among students and their implications for health education - Janiola, Emma A. 1946-
This study aimed to look into the use of alcoholic beverages among the students of the Bohol Agricultural College. Specifically, it sought to determine the extent and prevalence of the use of alcoholic beverages among the students and the implications of the findings of this study on alcohol education.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: Alcohol and youth -- Bohol; Health education -- Philippines